Monte Carlo Simulation Of Estimating Clean Water Supplies - Walid, Fajari Husnul; Dur, Sajaratud; Aprilia, Rima (ZERO: Jurnal Sains, Matematika dan Terapan, 2021)
Estimates are important tools in effective and efficient planning for predicting future events. Identical estimates of the future values of a variable for planning or decision making of a situation to estimate future values. Monte Carlo simulation is a simulation model that involves a series of random and sampling with a probability distribution that can be known and determined, then this simulation can be used. In this study, data is taken from the amount of water usage in PDAM Tirtanadi H.M branch. Yamin, North Sumatra from January 2018 to June 2019. Then, the data is processed and analyzed using Monte Carlo Simulation to determine the forecast results in the years that follow. The result is an estimated amount of water usage in 2019 and 2020 at PDAM Tirtanadi H.M branch. Yamin, North Sumatra is 8,604,556 and 8,592,873. The estimated amount of water use is down from the amount of water use in 2018 which reached 8,685,356. The amount of water usage in 2018, 2019 and 2020 decreases by about .